Stability of Chemically Passivated Silicon Electrodes in Aqueous Solutions: Interplay between Bias Voltage and Hydration of the Electrolyte - Gonçales, V.; Wu, Y.; Gupta, B.; Parker, S.; Yang, Y.; Ciampi, Simone; Tilley, R.; Gooding, J. (American Chemical Society, 2016)
Chemical passivation of nonoxide semiconductors is a key prerequisite for electrochemical devices that operate in water-based electrolytes. Silicon remains the technologically most important material and organic monolayers based on the hydrosilylation of 1-alkynes have been shown to be a very effective approach to limit the thermodynamically favorable oxidation of the electrode, while still retaining efficient electron transfer across the solid/liquid interface. A large excess of a supporting electrolyte is always added to the solution in order to confine the applied potential gradient to the region close to the surface of the electrode. However, little is known about how the degree of solvation of the electrolyte species is linked to the degradation of the passivating chemistry. Here we test experimentally how electrolytes with different intrinsic hydration levels can influence the protection of the silicon as a function of surface biasing. X-ray photoelectron spectroscopy and contact angle experiments are used to determine under which conditions the chemical protection breaks down and oxidation of the silicon begins. Our results suggest that (i) anions seem to have a bigger impact on the growth of oxide than cations and (ii) the surface chemistry is more effective for protecting the semiconductor surface against oxidation in the presence of weakly hydrated ions. The utilization of strongly hydrated ions as the electrolyte dramatically diminishes the potential range in which the organic monolayer protects the silicon in aqueous environments.